Temporary Adjustment or Normative Change? Fertility and Marriage Preferences of Syrian Refugees in Turkey in the Context of Forced Migration - Bozdag, Ilgi; Sierra-Paycha, Celio; Andro, Armelle (Frontiers in Human Dynamics, 2022)
Turkey has the highest number of refugees in the world and is currently home to 3.7 million Syrians who had to flee from their country due to the conflict that started in 2011. This paper aims to focus on the fertility and marriage preferences of Syrian refugees by using a widely used qualitative research method Focus Group Discussions. The main findings revealed that socio-demographic indicators, the departure and arrival conditions in home and host country and the current place of residence had affected how families and individuals adjusted themselves and how they changed their fertility and marriage plans since their arrival in Turkey. Yet, the main findings also showed that while forced migration caused normative changes on some, some others reacted and saw these changes just as a temporary adjustment.